Corilagin Interferes With Toll-Like Receptor 3-Mediated Immune Response in Herpes Simplex Encephalitis - Li, Lu-Jun; Zhang, Shao-Jun; Liu, Pan; Wang, You-Qin; Chen, Zhi-Lin; Wang, Yu-Jie; Zhou, Jia-Bin; Guo, Yuan-Jin; Zhao, Lei (Frontiers in Molecular Neuroscience, 2019)
Herpes simplex virus encephalitis (HSE) is the most common infectious disease of the central nervous system (CNS) in the worldwide. However, the pathogenesis of HSE is not clear. Research has reported that the immune response mediated by the TLR3 signaling pathway is an essential immune response to CNS against HSV infection. But if it is overreacted, it will cause tissue damage and related pathological changes. The aim of this study was to explore the molecular mechanism of Corilagin to control HSE by controlling TLR3 signaling pathways in vitro and in vivo. When cells and mice were activated by Polyriboinosinic polyribocytidylic acid (poly (I:C)) or HSV-1, and then treated with Corilagin, the mRNA and protein levels of TLR3, TRIF, TRADD, TRAF3, TRAF6, NEMO, P38, IRF3 were decreased. Interleukin (IL)-6, tumor necrosis factor-alpha (TNF-α), type 1 IFN (IFN-β) were also decreased. Furthermore the expression of TLR3 molecule was silenced or over-expressed, Corilagin could still inhibit the expression of TLR3 and downstream mediators. Additionally the mice brain tissues were measured by immunohistochemistry and haematoxylin-eosin (HE) staining and immunohistochemical (IHC), Corilagin could lessen the degree of brain inflammation. This results indicate that Corilagin can regulate the immune response in the pathogenesis of HSE and relieve inflammatory injury by affecting the TLR3 signaling pathway.